EFFECT OF SPACING, TREES CROWN SHAPE AND THE WAY OF PLANTING ON GROWTH AND YIELDING OF TWO CULTIVARS OF PEACHES - Adam Szewczuk; Ewelina Gudarowska (Acta Scientiarum Polonorum: Hortorum Cultus, 2012)
One of the factors, determining early bearing of peach trees is planting them in high density. But it is difficult, because of the use of generative, strong growing rootstock. However the intensive growth of peach trees can be modified by planting in ridges and changing the shape of crown. The experiment was conducted in conditions of Lower Silesia Region. The experiment involved the assessment of trees on Manchurian peach rootstock, of ‘Suncrest’ and ‘Cresthaven’ cultivars, planted in the spring 2006, in: 3.5 × 1 m spacing (vertical axis) 3.75 × 2 m (spindel crown) and 4.25 × 3 m (open vase crown). Half of the trees following 3.5 × 1 m spacing were planted in a traditional way, while half of them, in ridges. The aim of research was determination of possibilities regarding the maintenance of the peach orchard on a seedling rootstock, with the use of a vertical axis crown form and the way of planting trees in ridges, as compared to trees planted traditionally and trained as spindle and an open vase crown. Summary yields from the first three years of yielding point to the possibility of obtaining high yield of peaches at dense trees planting in comparison to traditional model of peach orchard. The lowest yielding level characterized trees of both examined varieties planted in 4.25 × 3 m spacing and trained in the form of an open vase crown. The most intensive growth featured the trees trained in the form of an open vase crown and planted in 4.25 × 3 m spacing. Planting in ridges did not cause any significant diversity regarding peaches growth and yielding in high density of trees trained as vertical axis.